THE REBELLION OF THE BORN UNFREES: FALLISM AND THE NEO-COLONIAL CORPORATE UNIVERSITY (The Strategic Review for Southern Africa, 2020)
South Africa's public discourse has been largely influenced by the recent student protests in higher education. Government officials, student leaders, higher education officials and the general populance have all participated in this national debate. This youth activism is led by various student political formations using the popular slogan of 'FeesMustFall' to mobilise their peers and broader society. Student leaders argue that the main strategic objective is to achieve free decolonised higher education. This article explores the socio-economic and political context driving these student marches across the country. It argues that the protest action is primarily caused by the following two phenomena: first, the broader societal discontent with persistent class, race and gender inequalities in South Africa. Second, the negative socio-economic impacts of a neo-colonial corporatised higher education model. The student demands are discussed in relation to these two broad structural trends associated with the transition to liberal democracy in South Africa. My core contention is that the student movement proposals are crucial for restructuring the neo-colonial corporate university.
Keywords: rebellion; South Africa; student protests; higher education; national debate; youth activism; student political formations; FeesMustFall; free decolonised higher education; decolonisation; socio-economic; political; class inequalities; gender inequalities; race inequalities; societal discontent; neo-colonialism; corporatised higher education model; liberal democracy; fallism; born free myth; political justice; non-racialism; neo-apartheid; human development index; epistemic coloniality; market colonisation; authoritarianism; cheap labour; patriarchy; intersectionality